Different approaches to the Composition of Neutron Stars and their Environment - Avellar, Marcio Guilherme Bronzato de (2012)
Even after 80 years of intense research, the composition of neutron stars remains unknown, since both the dense matter in the interior of these compact objects and the matter moving around them are in extreme physical conditions, unreproducible in terrestrial laboratories. In this Thesis, we follow four different interconnected ways to approach these extreme objects. First, we explore the mathematical structure of neutron stars, building solutions parametrised solely by the central density, what are very appropriate to study the structural behaviour of these stars in different situations. Then, we adopted a novel approach, the information theory, to infer a hierarchy of equations of state, showing that quark stars would be, by its configuration, favoured by Nature. Studying the X-ray emission arising from the low-mass binary system 4U 1608-52, which contains a neutron star, we limit the physical size of the emitting source, showing that it should not be far from the surface of the compact star. For this, we employed a technique to calculate the time lags never used before. Finally, we show that it is possible to obtain restrictions on the strange quark mass and the energy gap of the CFL directly from observations. We conclude this Thesis with the statement that the strange quark matter is, structurally and energetically favoured by Nature, though there is an entropic barrier to be overcame and a minimum central density to be reached just after the collapse of the progenitor star. If this barrier is actually overcame in Nature, only refined observations will tell.